SEASONAL CHANGES IN THE BIOCHEMICAL COMPOSITION OF LIVER IN GARRA MULLYA(SYKES) - SOMVANSHI, V S (Fishery Technology, 2017)
Seasonal changes taking place in the biochemical constituents of liver of G. mullya are reported. An inverse relationship was noticed in the variation of fat and water. Maximum fat contents were observed during June-July. Reserve fat was utilised Â·through gluconeogenesis during the spawning months. Protein and glycogen percentages were comparatively higher in liver than in the muscles and gonads. Decline in the glycogen content was associated with spawning during July to November. Nutritive values have shown more energy contents in the liver during pre-spawning months.